“It is the left eye, right?” - Pikkel, Dvora (Dove Medical Press, 2014)
OBJECTIVE: Because wrong-site confusion is among the most common mistakes in the operations of paired organs, we have examined the frequency of wrong-sided confusions that could theoretically occur in cataract surgeries in the absence of preoperative verification. METHODS: Ten cataract surgeons participated in the study. The surgeons were asked to complete a questionnaire that included their demographic data, occupational habits, and their approach to and the handling of patients preoperatively. On the day of operation, the surgeons were asked to recognize the side of the operation from the patient’s name only. At the second stage of the study, surgeons were asked to recognize the side of the operation while standing a 2-meter distance from the patient’s face. The surgeons’ answers were compared to the actual operation side. Patients then underwent a full time-out procedure, which included side marking before the operation. RESULTS: Of the total 67 patients, the surgeons correctly identified the operated side of the eye in 49 (73%) by name and in 56 (83%) by looking at patients’ faces. Wrong-side identification correlated with the time lapsed from the last preoperative examination (P=0.034). The number of cataract surgeries performed by the same surgeon (on the same day) also correlated to the number of wrong identifications (P=0.000). Surgeon seniority or age did not correlate to the number of wrong identifications. CONCLUSION: This study illustrates the high error rate that can result in the absence of side marking prior to cataract surgery, as well as in operations on other paired organs.